Optimal adaptive higher order controllers subject to sliding modes for a carrier system. (15th June 2018) - Jahanshahi, Hadi; Sari, Naeimeh Najafizadeh; Pham, Viet-Thanh; Alsaadi, Fawaz E; Hayat, Tasawar
Due to costly space projects, affordable flight models and test prototypes are of incomparable importance in academic and research applications, for example, data acquisition and subsystems testing. In this regard, CanSat could be used as a low-cost, high-tech, and lightweight model. CanSat carrier launch system is a simple second-order aerospace system. Aerospace systems require the highest level of effective controller performance. Adding second-order integral and second-order derivative terms to proportional–integral–derivative controller leads to the elimination of steady-state errors and yields to a faster systems convergence. Moreover, sliding mode control is considered as a robust controller that has appropriate features to track. Thus, this article tends to present an adaptive hybrid of higher order proportional–integral–derivative and sliding mode control optimized by multi-objective genetic algorithm to control a CanSat carrier launch system.